Pengembangan Kurikulum Berbasis STEAM (Science, Technology, Engineering, Arts, and Mathematics) untuk Meningkatkan Kreativitas dan Kemampuan Berfikir Kritis - Iffiani, Zelly; Chaerunnisa; Surudin, Yan; Rosdianto; Ngabidin; Ika Kartika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In learning process activities, the curriculum is really needed as a guide to setting targets and making the teaching and learning process easier. The curriculum will be easy to implement through several approaches, one of which is a STEAM (Science, Technology, Engineering, Arts, and Mathematics) based approach. This research aims to analyze the development of a STEAM-based curriculum to increase creativity and critical thinking skills. The research method used is the literature review method. Sources of information can be books, journals, ebooks, or other scientific articles. The results of this research are that the STEAM approach is able to increase students' creativity and critical thinking power. The STEAM learning model is a learning innovation that can be applied at all levels of education. It is designed to equip students with various skills to face various changes in the world, including the challenges of advances in science and technology in the field of education.